The Economic Burden of Schizophrenia in the United States in 2013 - Cloutier, Martin; Aigbogun, Myrlene Sanon; Guerin, Annie; Nitulescu, Roy; Ramanakumar, Agnihotram V; Kamat, Siddhesh A; DeLucia, Michael; Duffy, Ruth; Legacy, Susan N; Henderson, Crystal; Francois, Clement; Wu, Eric (The journal of clinical psychiatry, 2016)
The objective of this study was to estimate the US societal economic burden of schizophrenia and update the 2002 reported costs of $62.7 billion given the disease management and health care structural changes of the last decade. A prevalence-based approach was used to assess direct health care costs, direct non-health care costs, and indirect costs associated with schizophrenia (ICD-9 codes 295.xx) for 2013, with cost adjustments where necessary. Direct health care costs were estimated using a retrospective matched cohort design using the Truven Health Analytics MarketScan Commercial Claims and Encounters, Medicare Supplemental, and Medicaid Multistate databases. Direct non-health care costs were estimated for law enforcement, homeless shelters, and research and training. Indirect costs were estimated for productivity loss from unemployment, reduced work productivity among the employed, premature mortality (ie, suicide), and caregiving. The economic burden of schizophrenia was estimated at $155.7 billion ($134.4 billion-$174.3 billion based on sensitivity analyses) for 2013 and included excess direct health care costs of $37.7 billion (24%), direct non-health care costs of $9.3 billion (6%), and indirect costs of $117.3 billion (76%) compared to individuals without schizophrenia. The largest components were excess costs associated with unemployment (38%), productivity loss due to caregiving (34%), and direct health care costs (24%). Schizophrenia is associated with a significant economic burden where, in addition to direct health care costs, indirect and non-health care costs are strong contributors, suggesting that therapies should aim at improving not only symptom control but also cognition and functional performance, which are associated with substantial non-health care and indirect costs.